Dynamics of protest and electoral politics in the Great Recession - Björn Bremer; Swen Hutter; Hanspeter Kriesi (European Journal of Political Research, 2020)
This article links the consequences of the Great Recession on protest and electoral politics. It innovates by combining the literature on economic voting with social movement research and by presenting the first integrated, large-scale empirical analysis of protest mobilisation and electoral outcomes in Europe. The economic voting literature offers important insights on how and under what conditions economic crises play out in the short-run. However, it tends to ignore the closely connected dynamics of opposition in the two arenas and the role of protests in politicising economic grievances. More specifically, it is argued that economic protests act as a `signalling mechanism' by attributing blame to decision makers and by highlighting the political dimension of deteriorating economic conditions. Ultimately, massive protest mobilisation should, thus, amplify the impact of economic hardship on the electoral losses of incumbents and mainstream parties more generally. The empirical analysis to study this relationship relies on an original semi-automated protest event dataset combined with an updated dataset of electoral outcomes in 30 European countries from 2000 to 2015. The results indicate that the dynamics of economic protests and electoral punishment are closely related and point to a destabilisation of European party systems during the Great Recession.
Keywords: 330; protest politics; protest event analysis; economic crisis; electoral politics; economic voting; mainstream parties